Librarians building innovative mobile technologies: Creating it ourselves. Issue 2 (3rd April 2019) - Morgan, Rebecca J.; Gipson, Tiffney A.; Robinson, Lauren E.
Abstract: As patrons increasingly rely on mobile applications and responsive websites to access information, it has become imperative that libraries accommodate these needs. Although building these resources in-house may seem too expensive, time-consuming, and require outsourcing, this paper showcases how it can be achieved on a small scale using existing staff, innovative funding resources, and affordable training.